Valuation, Synergy, Exit Strategy Analysis of the Potential Grab-Goto Merger: A Strategic Financial Perspective - Vega Amarazka (Syntax Corporation, 2026)
This study explores the financial feasibility of a potential merger between Grab and GoTo, two leading digital platform companies in Indonesia with overlapping services in mobility, food delivery, and payments. Despite their scale, both firms continue to record significant losses due to duplicated operations and high customer acquisition costs. As investors shift focus from growth to profitability, a merger presents a possible path to efficiency. The research applies a quantitative approach using Discounted Cash Flow (DCF) and Free Cash Flow to Firm (FCFF) methods to project standalone valuations over five years. Synergies are then estimated based on cost savings and potential revenue improvements from operational integration. The combined enterprise value is compared to the sum of standalone values to assess merger benefits. Two simplified exit strategies are modeled: (1) an Initial Public Offering (IPO) using EV/Revenue multiples, and (2) a Strategic Sale using EV/EBITDA multiples. These provide insight into how investors might realize value post-merger. Findings suggest the merger could generate meaningful synergies and enhance financial attractiveness, though subject to execution risk and regulatory constraints. While the analysis is limited to financial modeling based on public data, it offers early-stage insights for decision-makers assessing strategic consolidation in the digital sector.